C / C composite material and high-temperature alloy TLP diffusion welding connecting material and connecting method
By using Co-Fe-B system eutectic alloy as the connecting material and combined with TLP diffusion welding technology, the problems of poor high temperature resistance and low reliability of the connection between C/C composite materials and high-temperature alloys are solved, and the connection is achieved at a lower level The effect of high temperature resistant and high reliability joints is obtained at temperatures.
Patent Information
- Application Number
- CN202411645486.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-07
AI Technical Summary
The problem of poor high temperature resistance and low reliability of C/C composite materials and high temperature alloy connection joints.
Co-Fe-B system eutectic alloy is used as the connecting material, and a high-temperature resistant joint is formed at a lower connection temperature through TLP diffusion welding technology. The connecting material includes 25% to 45% Fe, 1% to 6% B, and a balance of Co., which can be interdifferenced with cobalt-based, nickel-based and iron-based high-temperature alloys to improve the heat resistance of the joint.
High temperature resistant and high reliability joints are obtained at lower connection temperatures. The connection process is simple and the joint strength is high, which can meet the high temperature service needs in the aerospace field.
Smart Images

Figure CN119387954A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of dissimilar material connection, in particular to a C / C composite material and a high-temperature alloy TLP diffusion welding connection material and a connection method. Background Art
[0002] C / C composite materials have a series of excellent properties such as low density, high temperature resistance, low thermal expansion coefficient and wear resistance / erosion resistance, and have important application value in the new generation of aerospace aircraft and strategic missiles. However, due to the high brittleness of C / C composite materials themselves, high production costs, and difficulty in processing into complex parts, in practical applications, C / C composite materials often need to be combined with metals to form composite parts. High-temperature alloys have high high-temperature strength, good oxidation resistance and corrosion resistance, and are widely used in the aerospace field. Realizing reliable connection between C / C composite materials and high-temperature alloys is of great significance to the promotion and application of C / C composite materials and the development of aerospace aircraft and strategic missiles with high thrust-to-weight ratio and high sensitivity.
[0003] Due to the large difference in the thermophysical properties of C / C composite materials and high-temperature alloys and the fact that joints are often used in high-temperature environments, this type of connection has the problems of low reliability and poor high-temperature resistance. Active brazing has become a widely used connection technology for connecting C / C composite materials and metals because of its simple connection method. High-temperature active brazing filler metals can be used as connection materials to obtain high-temperature resistant joints. For example, the Chinese invention patent with publication number 202110765195.9 discloses an ultra-high-temperature brazing filler metal for connecting C / SiC composite materials and niobium alloys, its preparation process and vacuum active brazing method. In order to obtain high-temperature resistant C / SiC composite materials and Nb alloy joints, high-temperature resistant Ti-Cr-V is used as a connection material to connect C / SiC composite materials and Nb alloys at a connection temperature of 1440-1500°C. In theory, the use of high-melting-point brazing filler metals can improve the heat resistance of the joints, but at ultra-high connection temperatures, it will not only increase the thermal stress of the joints and reduce the reliability of the joints, but also have an adverse effect on the structure of the welded metal.
[0004] Transient liquid phase (TLP) diffusion welding uses materials with special components as connecting materials. During the connection process, atomic diffusion occurs between the liquid phase connecting material and the base material, thereby changing the composition of the connecting material. The liquid phase connecting material gradually achieves isothermal solidification, and finally obtains a joint with a heat resistance temperature higher than the connection temperature, that is, it can be "low temperature connection / high temperature service". However, at present, TLP diffusion welding is mainly used for connecting metals, and is rarely used to connect ceramic matrix composites and metals, especially C / C composites and high temperature alloys.
[0005] Therefore, it is necessary to develop a connecting material for transient liquid phase diffusion welding of C / C composite materials and high-temperature alloys to obtain high-temperature resistant and high-reliability joints at a lower connecting temperature. Summary of the invention
[0006] In order to solve the problems of poor high temperature resistance and low reliability of C / C composite material and high temperature alloy connection joints in the prior art, the present invention provides a C / C composite material and high temperature alloy TLP diffusion welding connection material and a connection method.
[0007] In order to achieve the above object, the specific scheme adopted by the present invention is:
[0008] On the one hand, the present invention discloses a TLP diffusion welding connection material for a C / C composite material and a high-temperature alloy, wherein the connection material is a Co-Fe-B alloy; in terms of mass fraction, it includes the following elements: 25% to 45% Fe, 1% to 6% B, and the remainder Co. Due to the infinite solid solution of the three elements Co, Ni, and Fe, the Co-Fe-B connection material is easy to diffuse with the cobalt-based high-temperature alloy, the nickel-based high-temperature alloy, and the iron-based high-temperature alloy. In addition, the B element, as a melting-reducing element of the connection material, has a small atomic radius and is easy to diffuse into the high-temperature alloy, so the eutectic point composition can change quickly, thereby improving the heat resistance of the joint. The Fe element, as a weak carbide-forming element, reacts mildly with the C / C composite material to form a discontinuous compound layer reaction layer, which reduces the brittleness of the C / C composite material side reaction layer, and is conducive to long-term heat preservation of the joint to improve the heat resistance of the joint.
[0009] Furthermore, the connection material is a Co-Fe-B eutectic alloy, and in terms of mass fraction, the connection material includes the following elements: 34.6% Fe, 4.5% B, and the balance Co. On the other hand, the present invention discloses a method for TLP diffusion welding of a C / C composite material and a high-temperature alloy, which is characterized by mainly comprising the following steps: S1. Grind the C / C composite material and high-temperature alloy with 240-800 grit sandpaper, and put the ground base material to be welded into anhydrous ethanol for ultrasonic cleaning; S2, assembling the C / C composite material, the connecting material and the high-temperature alloy from top to bottom into a "sandwich"-shaped welded part; S3. Place the workpiece to be welded in a vacuum furnace for TLP diffusion welding. After the insulation is completed, cool the furnace to below 120°C and open the furnace for sampling.
[0010] Furthermore, in step S3, the specific process of TLP diffusion welding is as follows: the connection temperature is 1100°C to 1250°C, the holding time is 70 to 180 minutes, and the vacuum degree is better than 5×10 -3 Pa.
[0011] Furthermore, the high-temperature alloy is a cobalt-based high-temperature alloy, a nickel-based alloy or an iron-based high-temperature alloy.
[0012] Furthermore, the connecting material is in foil or powder form.
[0013] Beneficial effects: In order to solve the shortcomings of the connection technology between C / C composite materials and high-temperature alloys, the present invention provides a C / C composite material and high-temperature alloy transient liquid phase diffusion welding connection material and connection process. The present invention adopts Co-Fe-B alloys with eutectic points and near-eutectic components as connection materials. During the connection process, liquid phase Co-Fe-B reacts with the C / C composite material to form a discontinuous brittle compound reaction layer; at the same time, Co-Fe-B and the high-temperature alloy diffuse atomically with each other, the melting element B in the connection material diffuses into the high-temperature alloy, and the elements such as Ni, Co, and Fe in the high-temperature alloy diffuse into the connection layer, causing the components of the connection material to change and gradually undergo isothermal solidification. The present invention has the advantages of obtaining a high-temperature resistant joint at a relatively low connection temperature, a simple connection process, and high joint strength. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 It is a flow chart of the connection method in the present invention.
[0015] Figure 2 This is the organizational diagram of the powdered connecting material in Example 1, and the particle size is -300 mesh.
[0016] Figure 3 This is the microstructure diagram of the joint obtained in Example 1.
[0017] Figure 4 This is an enlarged view of the interface of the joint obtained in Example 1 on the C / C composite material side. DETAILED DESCRIPTION
[0018] The technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0019] Example 1 The connecting material used in this embodiment is a Co-Fe-B eutectic alloy in powder form. In terms of mass fraction, the connecting material includes the following elements: 34.6% Fe, 4.5% B, and the balance Co. Figure 2 is the organizational diagram of the connection material, Figure 2 It can be seen that the powdered alloy is spherical as a whole, with a smooth surface and a size less than 50 μm.
[0020] Please refer to Figure 1 The specific method of using transient liquid phase diffusion welding of C / C composite material and GH5188 cobalt-based high-temperature alloy using the upper connection material is: S1. Use wire cutting to cut the C / C composite material and GH5188 cobalt-based high-temperature alloy into 5mm×5mm×5mm and 10mm×10mm×4mm specimens respectively. Then use 1500-mesh sandpaper to grind the C / C composite material and 240-mesh sandpaper to grind the high-temperature alloy. Use anhydrous ethanol ultrasonic cleaning for 5 minutes after the grinding of the base material to be welded. S2. The connecting material is mixed with ethylene glycol into a paste, and pre-placed between the C / C composite material and the GH5188 high-temperature alloy to form a welded part, wherein the upper part is the C / C composite material and the lower part is the GH5188 high-temperature alloy; S3. Instantaneous liquid phase diffusion welding is performed on the parts to be welded in a vacuum brazing furnace. The connection temperature is 1140℃, the holding time is 90min, the heating rate is 10℃ / min, and the vacuum degree is better than 5×10 -3 Pa, after the insulation is completed, cool down with the furnace to below 120℃ and take out the sample.
[0021] In order to characterize the quality of the connection joint of the present invention, the joint structure after welding was observed and analyzed. The joint was cut in the middle by a wire cutting machine, and a metallographic sample was made, and the joint structure was observed by a scanning electron microscope. Figure 3 The overall organizational structure of the joint obtained in Example 1 is shown in FIG. Figure 4 The middle is an enlarged view of the interface reaction layer on the C / C composite material side. Figure 3 and Figure 4 It can be seen that the C / C composite material and the GH5188 high-temperature alloy are firmly connected through the connecting layer.
[0022] Example 2
[0023] The difference between this embodiment and embodiment 1 is that in step S3, the insulation time is 120 minutes.
[0024] Example 3
[0025] The difference between this embodiment and embodiment 1 is that the parent material is a C / C composite material and a GH3044 nickel-based high-temperature alloy.
[0026] Example 4
[0027] The difference between this embodiment and embodiment 1 is that the parent material is a C / C composite material and a GH2036 iron-based high-temperature alloy.
[0028] Comparative Example 1
[0029] The difference between this comparative example and Example 1 is that the connecting material used in this example is a Co-Fe-B alloy in powder form, and the connecting material includes the following elements by mass fraction: 20% Fe, 0.8% B, and the balance Co.
[0030] Comparative Example 2
[0031] The difference between this comparative example and Example 1 is that the connecting material used in this example is a Co-Fe-B alloy in powder form, and the connecting material includes the following elements by mass fraction: 50% Fe, 7% B, and the balance Co.
[0032] Comparative Example 3
[0033] The difference between this comparative example and Example 1 is that in step S3, the connection temperature is 1080°C.
[0034] Comparative Example 4
[0035] The difference between this comparative example and Example 1 is that in step S3, the connection temperature is 1300°C.
[0036] Comparative Example 5
[0037] The difference between this comparative example and Example 1 is that in step S3, the insulation time is 60 minutes.
[0038] Comparative Example 6
[0039] The difference between this comparative example and Example 1 is that in step S3, the insulation time is 240 min.
[0040] The joints obtained in Examples 1-4 and Comparative Examples 1-6 were tested below, and the test results were examined.
[0041] In order to characterize the mechanical properties of the joint, the shear strength test of the joint was carried out. The joint was placed in a homemade shear mold and a shear test was carried out on an electronic universal testing machine. The loading rate of the testing machine was 0.5 mm / min, and the maximum compressive load was recorded and finally converted into the shear strength of the joint. In order to characterize the heat resistance of the joint, the heat resistance temperature of the joint connection layer was tested. The connection layer sample was prepared by wire cutting + grinding, and the initial liquefaction temperature of the connection layer was tested by TG-DSC comprehensive analyzer. The test results of shear strength and initial liquefaction temperature are shown in Table 1.
[0042] Table 1 Test results of joint shear strength and initial liquefaction temperature of the connecting layer obtained in Examples 1-4 and Comparative Examples 1-6
[0043] As shown in Examples 1-4 in Table 1, when the eutectic Co-34.6Fe-4.5B connecting material is used to connect C / C composite materials and high-temperature alloys (cobalt-based high-temperature alloys, nickel-based high-temperature alloys and iron-based high-temperature alloys), when the holding time is 90min and 120min, the initial liquefaction temperature of the connecting layer is higher than the connecting temperature, and "low-temperature connection / high-temperature service" is achieved. The joint strength is the highest at 1140℃×90min, reaching 45.7MPa. As shown in Comparative Examples 1-2, when the connecting material is Co-25Fe-0.8B, due to the low B element and high melting point of the connecting material, the connection cannot be achieved; when the connecting material is Co-45Fe-7B, the B element content is high, the initial liquefaction temperature of the connecting layer is lower than the connecting temperature, and "low-temperature connection / high-temperature service" cannot be achieved. From Comparative Examples 3-4, it can be seen that when the connection temperature is 1080°C, the connection material does not melt during the connection process and the connection cannot be achieved; when the connection temperature is 1300°C, although the initial liquefaction temperature of the connection layer is higher than the connection temperature, the higher connection temperature will introduce greater thermal stress into the joint, which is not conducive to the mechanical properties of the joint and has a negative impact on the microstructure of the high-temperature alloy parent material. From Comparative Examples 5-6, it can be seen that when the holding time is 60min (less than 70min), the joint performance is low, the initial liquefaction temperature of the connection layer is lower than the connection temperature, and "low temperature connection / high temperature service" is not achieved; when the holding time is 240min, although "low temperature connection / high temperature service" can be achieved, long-term holding will also have an adverse effect on the performance of the parent material.
[0044] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any equivalent changes or modifications made according to the essence of the present invention should be included in the protection scope of the present invention.
Claims
1. C / C composite material and high temperature alloy TLP diffusion welding connection material, characterized in that: The connecting material is a Co-Fe-B alloy, which comprises the following elements by mass fraction: 25% to 45% Fe, 1% to 6% B, and the balance Co.
2. The C / C composite material and high temperature alloy TLP diffusion welding connection material according to claim 1, characterized in that: The connecting material is a Co-Fe-B eutectic alloy, and in terms of mass fraction, the connecting material includes the following elements: 34.6% Fe, 4.5% B, and the balance Co.
3. A TLP diffusion welding method for connecting C / C composite materials and high-temperature alloys, characterized in that: The main steps are as follows: S1. Grind the C / C composite material and high-temperature alloy with 240-800 grit sandpaper, and put the ground base material to be welded into anhydrous ethanol for ultrasonic cleaning; S2. Assemble the C / C composite material, the connecting material and the high-temperature alloy from top to bottom into a "sandwich"-shaped welded part; S3. Place the workpiece to be welded in a vacuum furnace for TLP diffusion welding. After the insulation is completed, cool the furnace to below 120°C and open the furnace for sampling.
4. The TLP diffusion welding method for connecting a C / C composite material to a high-temperature alloy according to claim 3, characterized in that: In step S3, the specific process of TLP diffusion welding is as follows: the connection temperature is 1100°C to 1250°C, the holding time is 70 to 180 minutes, and the vacuum degree is better than 5×10 -3 Pa.
5. The TLP diffusion welding method for connecting a C / C composite material to a high-temperature alloy according to claim 3, characterized in that: The high temperature alloy is a cobalt-based high temperature alloy, a nickel-based alloy or an iron-based high temperature alloy.
6. The TLP diffusion welding method for connecting a C / C composite material to a high-temperature alloy according to claim 3, characterized in that: The connecting material is in foil or powder form.
Citation Information
Patent Citations
An ultra-high temperature brazing filler metal for joining C / SiC composite materials and niobium alloys, its preparation process and vacuum active brazing method
CN113478122B